A mutação constitucional na crise do positivismo jurídico: história e crítica do conceito no marco da teoria do direito como integridade - Flávio Barbosa Quinaud Pedron (2011)
The research begins from the current discussion about the rhetorical use of the constitutional change (Verfassungswandlung) in Rcl. n. 4335/AC in the Brazilian Supreme Court revisiting such theory and seeking to reflect on the Koselleck's Conceptual History as a valid theoretical framework. This reflection proves to be important to understand not only the origin of this concept, but the historical and legal context in which it was coined and its developments. Observing this, one should realize that the theory of constitutional change is essentially a typical strategy resource from the crisis of legal positivism to justify decisions that violate the constitutional order for political goals. Assuming a hermeneutic comprehension, especially through Dworkin’s theory, it became clear that the theory of constitutional changes lacks of democratic legitimacy, ignoring or sometimes misunderstanding the existence of a legal system that includes not only a set of rules but also legal principles. In the light of the transformations wrought the recognition of legal existence of the principles, it rests clear the fallacy of the arguments for constitutional change when confronted with the theory of law as integrity. This perspective provides a theory that better explains a conception of law concerned with democratic legitimacy of adjudication procedures and that is not anchored in the past, but is able to theorize legal evolution through an hermeneutic point of view.